COMPARING EFFECTIVENESS OF PALM DATES AND OXYTOCIN MASSAGE IN STIMULATING BREASTMILK PRODUCTION OF POST PARTUM MOTHER - Siti Roudhotul Jannah; Melyana Nurul Widyawati (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Backgrounds: The coverage of exclusive breastfeeding in the world is still low. It is influenced by the limited number of breastfeeding counselors, the lack of education, advocacy and coaching breastfeeding support groups, maternal health and physiological factors (prolactin and oxytocin hormones). Dates contains oxytocin and many chemical elements which are good for breastfeeding mothers. Regular oxytocin massage therapy is also shown to increase the production of the oxytocin hormone. Aims: To compare the effectiveness of palm dates and oxytocin massage in stimulating breastmilk production of postpartum mothers. Methods: it is a literature review study, using keywords breastfeeding, palm dates and oxytocin massage from national and international journals. Results: The results shown that palm date and oxytocin massage have been proven to increase the oxytocin hormone that is influential on the smoothness of breastfeeding in postpartum mothers. Some studies noted that the palm dates contain potuchin hormone that serves spur blood vessel contractions around the breast spurring mammary gland to produce milk. In addition, there is the hormone oxytocin can help stimulating the contractions of the muscles of the uterus to facilitate childbirth. While oxytocin massage can increase milk production and the baby's weight and also to drive a contraction in the veins surround the breast and spurring the milk glands to produce milk. Conclusion: The results of several studies suggest that the oxytocin massage is more effective applied to increase oxytocin than the consumption of palm dates.